Penyusunan Rencana Kegiatan Sekolah dan Rencana Anggaran Kegiatan Sekolah di SDIT Robbani Cendekia Ponorogo - Lestari, Agus (Lembaga Yasin AlSys, 2023)
Budgeting activities have two important aspects, namely revenue or revenue planning and expenditure. Thus, the budget of an institution can depict the activities or programs that will be or have been implemented, as well as the amount of expenses incurred, enabling the assessment of the effectiveness and efficiency of the programs listed in the budget. In this research, we focus on the financial management aspect of Education, specifically the issues related to the preparation of activity plans and school financing plans at SDIT Robbani Cendekia Ponorogo. This study adopts a qualitative approach, employing the field research method. The researchers actively gather data regarding the preparation of school activity plans and school budget plans through participant observation and interviews. The procedure for obtaining informants involves using purposive sampling techniques. Researchers then conduct on-site descriptions and undertake a literature study, examining various literatures, documents, and other works to refine this research. The process of preparing the School Activity Plan and the School Activity Budget Plan is carried out through an annual working meeting attended by all foundation officials and educational institution administrators (TPAIT, PGIT, TKIT, and SDIT), the school principal, teachers, and staff. During the budget preparation process, priority scales are set for the implementation of school programs. Additionally, consultations are held to reach a consensus on the required budget and the amount of funds that need to be raised from the community to execute the school programs. These consultations take place through commission meetings, and the outcomes are presented together at a plenary meeting to obtain approval from all organizational elements. Subsequently, all parents are invited to participate in a socialization event to inform them about the educational programs for the upcoming year.